Gene Therapy for Bone Repair Using Human Cells: Superior Osteogenic Potential of Bone Morphogenetic Protein 2–Transduced Mesenchymal Stem Cells Derived from Adipose Tissue Compared to Bone Marrow - Bougioukli, Sofia (Hum Gene Ther, 2018)
Ex vivo regional gene therapy strategies using animal mesenchymal stem cells genetically modified to overexpress osteoinductive growth factors have been successfully used in a variety of animal models to induce both heterotopic and orthotopic bone formation. However, in order to adapt regional gene therapy for clinical applications, it is essential to assess the osteogenic capacity of transduced human cells and choose the cell type that demonstrates the best clinical potential. Bone-marrow stem cells (BMSC) and adipose-derived stem cells (ASC) were selected in this study for in vitro evaluation, before and after transduction with a lentiviral two-step transcriptional amplification system (TSTA) overexpressing bone morphogenetic protein 2 (BMP-2; LV-TSTA-BMP-2) or green fluorescent protein (GFP; LV-TSTA-GFP). Cell growth, transduction efficiency, BMP-2 production, and osteogenic capacity were assessed. The study demonstrated that BMSC were characterized by a slower cell growth compared to ASC. Fluorescence-activated cell sorting analysis of GFP-transduced cells confirmed successful transduction with the vector and revealed an overall higher but not statistically significant transduction efficiency in ASC versus BMSC (90.2 ± 4.06% vs. 80.4 ± 8.51%, respectively; p = 0.146). Enzyme-linked immunosorbent assay confirmed abundant BMP-2 production by both cell types transduced with LV-TSTA-BMP-2, with BMP-2 production being significantly higher in ASC versus BMSC (239.5 ± 116.55 ng vs. 70.86 ± 24.7 ng; p = 0.001). Quantitative analysis of extracellular deposition of calcium (Alizarin red) and alkaline phosphatase activity showed that BMP-2-transduced cells had a higher osteogenic differentiation capacity compared to non-transduced cells. When comparing the two cell types, ASC/LV-TSTA-BMP-2 demonstrated a significantly higher mineralization potential compared to BMSC/LV-TSTA-BMP-2 7 days post transduction (p = 0.014). In conclusion, this study demonstrates that transduction with LV-TSTA-BMP-2 can significantly enhance the osteogenic potential of both human BMSC and ASC. BMP-2-treated ASC exhibited higher BMP-2 production and greater osteogenic differentiation capacity compared to BMP-2-treated BMSC. These results, along with the fact that liposuction is an easy procedure with lower donor-site morbidity compared to BM aspiration, indicate that adipose tissue might be a preferable source of MSCs to develop a regional gene therapy approach to treat difficult bone-repair scenarios.